2021
DOI: 10.1371/journal.pone.0259543
|View full text |Cite
|
Sign up to set email alerts
|

A pattern of platelet indices as a potential marker for prediction of pre-eclampsia among pregnant women attending a Tertiary Hospital, Ethiopia: A case-control study

Abstract: Introduction Preeclampsia is the most serious health risk during pregnancy for both the mother and the fetus. Even though platelet parameters are among the proposed biomarkers for the prediction of preeclampsia, the use of its indices in the diagnosis of preeclampsia is not increasing in Ethiopia. There is little information on platelet patterns in preeclampsia and normal pregnancy. The purpose of this study was to determine the pattern of platelet indices in women with preeclampsia in our study setting. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
2
5
1
Order By: Relevance
“…Similar ndings were observed in other studies. (21,22) The current study demonstrated that MPV and PDW values were signi cantly higher among cases compared to the control group, which is in line with the study conducted by Eman Abdel-Moneim Alkholy et al and Shaifali Dadhich et al (7,23) The rationale behind increased MPV and PDW could be stimulation of bone marrow for the production of new platelets due to the consumption of platelets at the injured sites. The newly produced platelets will be larger in size and more active both metabolically and enzymatically.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar ndings were observed in other studies. (21,22) The current study demonstrated that MPV and PDW values were signi cantly higher among cases compared to the control group, which is in line with the study conducted by Eman Abdel-Moneim Alkholy et al and Shaifali Dadhich et al (7,23) The rationale behind increased MPV and PDW could be stimulation of bone marrow for the production of new platelets due to the consumption of platelets at the injured sites. The newly produced platelets will be larger in size and more active both metabolically and enzymatically.…”
Section: Resultssupporting
confidence: 91%
“…Prior studies had different cutoffs, sensitivities and speci cities for the different hematological parameters to differentiate normotensive pregnant women from preeclamptic women, but PC/PDW was not performed in those studies. (21,22,28) In this study, PC/PDW was signi cantly decreased in PE cases compared to the control group and had the highest AUC of 0.767 (95% CI: 0.639-0.895) at the cutoff of 15.1 (sensitivity of 70.8%; speci city of 81.9%). The risk of PE was highest at this cutoff, i.e., 11fold higher (OR = 11.02; 95% CI: 3.79-31.99; P < 0.001), thus making PC/PDW the best marker of PE.…”
Section: Resultsmentioning
confidence: 53%
“…The prothrombin time (PT) showed a significant increase in pregnant with GH and non-pregnant with chronic HT in comparison to both the control and healthy pregnant, the results of the study are consistent with the study of Bawore et al (2021) of damage to the lining of blood vessels as a result of atherosclerosis caused by HT in these patients. This may be because the coagulation activities, anticoagulants, fibrinolysis, and antifibrinolytic activities are further enhanced during pregnancy.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, platelet count is higher in women with mild PE than severe PE; this indicates platelet count decreases with the severity of preeclampsia, but it is statistically insignificant compared with previous studies that illustrate that platelet count decreases in preeclampsia [ 10 , 25 ]. Platelet distribution width (PDW) and mean platelet volume (MPV) were 13.3 ± 2.3 fl.…”
Section: Discussioncontrasting
confidence: 70%